Assessment of vegetation cover dynamics in the agro-ecological Zones of Nigeria - Adeaga, Olusegun; Lawal, Odunayo; Adedeji, Oluwatola; Akinbaloye, Olutosin (Bulletin of Geography. Physical Geography Series, 2022)
The drastic vegetation loss of about 22% in 12 years across agro-ecological zones (AEZs) in Nigeria, which can be attributed to the impact of climate and anthropogenic activities on vegetation dynamics within the context of socio-economics, calls for concern. In this study, remotely sensed data from the European Space Agency Land Use/Land Cover dataset, TAMSAT rainfall data, and MODIS NDVI dataset were used to examine changes in vegetation dynamics and monitor vegetation health in the AEZs based on the Normalised Difference Vegetation Index (NDVI). The study showed that vegetation cover has been decreasing tremendously at an alarming rate in most of the zones, while different drivers (change agents) have been responsible for the losses. The analysis shows that, between 2003 and 2018, the forestland cover gained 9,768.88 km2 and lost 40,891.6 km2, with a total net decrease of 31,122.73 km2. Contribution to the net change in forestland is usually converted to wetland, urban, cropland and grassland, across the varied ecosystem. The need for upto-date and accurate land-cover information is key to developing an appropriate mitigation strategy within the context of socio-economic sustainability across AEZs in Nigeria.